Pengaruh Proses Pengolahan terhadap Kadar Pati Resisten Sukun (Artocarpus altilis Park) (Jurnal Teknologi Pangan, 2013)
A  study  on  the  effect  of  processing  on  resistant  starch  (RS)  content  of Breadfruit  (Artocarpus  altilis  Park)  has  been  conducted.  The  aim  of  this research was to evaluate a resistant starch formation in pre-cooked flour made of breadfruit using different processing methods. The principle of preparing the pre-cooked  flour  is  improving  retrograded  starch  content  which  is  a  kind  of resistant starch (type 3) The processing included boiling, steaming, and frying, and  each  processing  was  combined  with  cooling  for  24  hours  in  refrigerator, prior to drying, milling and shieving.  It  was  found  that  processing  (combination  of  heating  and  cooling)increased  Resistant  Starch  (RS)  content  of  breadfruit.  Boiling  and  cooling changed RS from 3.27%to 3.82% (16.8%),  steaming and cooling changed RS from 3.27% to 6.67%  (103.9%) and frying and cooling changed RS from 3.27% to  3.68%  (12.5%).  Pre-cooked  flour  from  the  best  treatment  (steaming  and cooling)  was   tried  to  be  applied  in  making  of  biscuit,  cakes  and  sweet  bread (with   various  formulation).  The  products  prepared  by  substitution  with  pre-cooked flour (until 30%) were preferred by the panels in term of color, taste  and texture and they have medium resistant starch content (2,5-5,0%), so that  they can be developed as the kind of functional food.Key  words  :  breadfruit,  processing  method,  pre-cooked  flour,  resistant  starch(RS), functional food